Topical Issues of Realization of the Principle of Self-determination of Peoples and Supremacy of Law in International Relations - T. S. Tsymbrivskyy (Московский журнал международного права, 2010)
The article is devoted to the issues of the contemporary realization of the principle of self-determination of peoples in international law. In this relation the research outlines that this principle belongs to one of the most contradictory principles of international law and on this ground in practice the realization of the principle requires сlear legal regulation. Both modern doctrine developments of the principle of self-determination of peoples and practice of international law in this area are examined in the article. As an outcome of the scientific research the author drew a conclusion that today is taking place a gradual institualization of international legal criteria of cesession which legalize the separation of administrative-territorial units from the state territory.